The Association between Disability and Psychosocial Issues in Individuals with Leprosy - Jatimi, Atika; Holisun, Holisun; Ahmadi, Ahmadi (Inspirasi Foundation, 2024)
Introduction: Leprosy is a disease that can cause physical disabilities, which in turn contribute to the emergence of psychosocial problems in affected individuals. Objective: This study aims to analyze the relationship between the level of disability and psychosocial problems among leprosy patients in the working areas of Jrengoan Health Center and Karang Penang Health Center. Method: This study employs an analytical observational design with a cross-sectional approach. The study population consists of all leprosy patients in the working areas of the two health centers, totaling 47 individuals. The sampling technique used is non-probability sampling with a purposive sampling method, resulting in 42 respondents who meet the inclusion criteria. Disability levels were measured using an observation sheet, while psychosocial problems were assessed through a questionnaire. Data analysis was conducted using the Spearman Rho statistical test. Result: The results of the crosstabulation analysis revealed that among patients with level 2 disabilities, 12 individuals (28.6%) experienced severe psychosocial problems, while 2 individuals (4.8%) had mild psychosocial issues. The Spearman Rho test indicated a relationship between disability occurrence and psychosocial problems, with a p-value of 0.043 > 0.05. These findings suggest that the higher the level of disability, the more severe the psychosocial problems experienced by leprosy patients. Conclusion: In conclusion, the majority of leprosy patients in this study had level 1 disabilities, but those with level 2 disabilities tended to experience more severe psychosocial issues. This reinforces the notion that as the degree of disability increases, the psychosocial impact on leprosy patients also becomes more significant.